Influence of Prognostic Factors on Lymph Node Involvement in Endometrial Cancer: A Single-Center Experience. Issue 6 (July 2018) - Widschwendter, Peter; Bauer, Emanuel; De Gregorio, Nikolaus; Bekes, Inga; Janni, Wolfgang; Scholz, Christoph; Friedl, Thomas W.P.
Abstract : Objective: The requirement for and extent of lymphadenectomy in endometrial cancer is still controversial. Clinicopathological prognostic factors could be helpful to predict lymph node involvement and avoid therefore unnecessary lymphadenectomy. The aim of this study was to investigate which factors can predict lymph node involvement and how lymph node metastases are distributed in the pelvic and para-aortic regions. Methods: This retrospective analysis was performed by analyzing data from patients with endometrial cancer treated with standard surgery and lymphadenectomy at the Department of Gynecology and Obstetrics of the University Hospital Ulm in 2000 to 2013. Results: One hundred twenty-five patients received pelvic lymphadenectomy with a median of 25 removed nodes, and 111 patients additionally received para-aortic lymphadenectomy with a median of 12 removed nodes. Metastatic lymph nodes were found in 24.8% of the patients, and a multivariate logistic regression showed that lymphovascular space invasion, histological type, and tumor stage significantly and independently predicted lymph node involvement. Of the 111 patients with both pelvic and para-aortic lymphadenectomy, 18 (16.2%) patients had metastatic para-aortic nodes, and 3 (2.7%) patients had isolated positive para-aortic lymph nodes without involvement of pelvic lymph nodes. Discussion: Lymphovascular space invasion, histological type, and tumor stage are significant predictors of lymph node involvement in endometrial cancer. In patients at high risk of nodal involvement, lymphadenectomy should be performed systematically up to the renal vein. Large and carefully designed prospective studies are needed to evaluate patient cohorts for which a complete lymphadenectomy provides a survival benefit. In the future, the increasing use of sentinel node biopsy may facilitate a more personalized treatment of patients with endometrial cancer.